A basic arthroscopy course based on motor skill training - AKMAN, MEHMET (SPRINGER, 2010)
Aim of this study is to introduce, evaluate, and propose a basic arthroscopy training course with interactive methods as using bovine knees, joint models but mainly focusing on practices with motor skill-learning devices. This study presents the results of a skill training program which is based on motor skill training theory and using bovine knees to simulate a specific task as arthroscopy both in education and evaluation. The participants gave feedback regarding their expectations, fulfillment, and self-evaluation on the degree of their improvement levels, after which their skills were evaluated by an expert while they performed the arthroscopic procedure. During this evaluation of the task, a four-dimensional checklist which was prepared previously by the consensus of three experts was used, and a global grading of each rater was added at the end of the checklist. In this 2-day course, small group teaching sessions are integrated with active and experiential learning methods consisting of short presentations by the educators, demonstrations using joint models and audio-visual teaching material, and significant continuous feedback by the teachers during the proceedings. Participants' expectations and post-course feedback results were obtained using a brief questionnaire which involved mostly open-ended questions. The self-rating of own basic diagnostic arthroscopy skill on a scale of 0-10 was completed by the participants both previous to and following the course to establish a student-centered learning environment. Overall rating of the course was asked on a 1-5 (poor excellent) Likert scale. The questioning of the participants who took part in the course during the last five terms involved a 100% feedback. The overall rating of the course was 4.36 +/- 0.47 on the 1-5 scale. The majority of the participants (90%) mentioned that the course met their expectations. The most beneficial activities were accepted to be the arthroscopic procedure applications on bovine knee, repetition of the manipulations under the supervision of the trainers, continuous feedback by experienced staff, and chance for immediate correction during the procedures (35/64). Pre- and post-course self-ratings of the participants inquiring about their ability to perform an arthroscopy alone showed significant improvement (4.2 vs. 7.7 P = 0.000, paired samples t test). All participants were found to be competent in the evaluation of their diagnostic arthroscopy skills on bovine knees. To design a skill teaching course based on the needs of the trainees, focusing on basic motor skill training exercises, and using bovine knee as a simulator is a safe, inexpensive, humanistic, and replicable method that proves a foundation for basic arthroscopic skills learning prior to patient encounter.
Keywords: Skill; Learning Basic motor skills; Bovine knee; Evaluation; Arthroscopy; EDUCATION